2016
DOI: 10.1007/s10508-016-0701-y
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Challenges and Rewards of Forming a Sexual Agreement Among HIV-Negative Male Couples

Abstract: Sexual agreements, explicit mutual understandings made between two partners about which sexual and related behaviors they agree to engage in within and/or outside of their relationship, are common among male couples. However, little is known about the perceived rewards and challenges partnered men face in the process of forming a sexual agreement. Such knowledge may be useful for development of future HIV preventive and sexual health programs that encourage male couples to establish a sexual agreement in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Both individual- and couple-level criteria were used to deem couples’ eligibility to participate in the study. Based on our prior work with male couples [ 34 , 35 ], we developed a system of decision rules to assess the verification of a couples’ relationship based on both partners’ responses to screener items (ie, to verify that a couple is in a relationship). Verification of couples’ relationships was based on data collected from both members of the couple and whether they concurred (ie, agreed) on certain predetermined eligibility screener items (see Figure 1 ), including (1) matching their relationship length within a margin of 1 month, (2) exact matching of each other’s birthday months, (3) matching each other’s ages within a margin of one year, and (4) exact matching of at least one of their two contact information options (eg, phone number, email address).…”
Section: Methodsmentioning
confidence: 99%
“…Both individual- and couple-level criteria were used to deem couples’ eligibility to participate in the study. Based on our prior work with male couples [ 34 , 35 ], we developed a system of decision rules to assess the verification of a couples’ relationship based on both partners’ responses to screener items (ie, to verify that a couple is in a relationship). Verification of couples’ relationships was based on data collected from both members of the couple and whether they concurred (ie, agreed) on certain predetermined eligibility screener items (see Figure 1 ), including (1) matching their relationship length within a margin of 1 month, (2) exact matching of each other’s birthday months, (3) matching each other’s ages within a margin of one year, and (4) exact matching of at least one of their two contact information options (eg, phone number, email address).…”
Section: Methodsmentioning
confidence: 99%
“…Mitchell et al found that MSM cited rewards of sexual agreements included honesty, communication, clear expectations, intimacy and trust. Challenges included stigma about having an open agreement; awkwardness and jealousy [ 79 ]. Hoff et al found positive relationship dynamics are associated with less risk with partners outside the relationship, but were associated with greater odds of condomless anal sex (CAS) with primary partners [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there is a fairly thorough understanding about what motivates male couples to establish a sexual agreement (Gass et al, 2012; Hoff & Beougher, 2010; Mitchell, Lee, Woodyatt, Bauermeister, Sullivan, & Stephenson, 2016), the actual process and context of how this formation occurs is lacking in the literature. By using qualitative dyadic data from 29 concordant HIV-negative male couples residing in either the Atlanta, GA or Detroit, MI metro areas, the present study sought to: 1) report when the sexual agreement in the relationship was formed at the individual- and couple-levels; 2) investigate the context and circumstances that led to couples to establish a sexual agreement (i.e., the process) at the individual- and couple-levels; and 3) describe whether the timing, contexts and circumstances that led couples to form a sexual agreement differed by their agreement type.…”
mentioning
confidence: 99%